The Relationship between Crude Oil Prices, Exchange Rate and Agricultural Commodity Price Returns Volatility in Nigeria: A Time Series Approach - David Adugh Kuhe; Tersoo Uba (Archives of Current Research International, 2018)
This paper examines the causal relationship between crude oil prices, Naira/US Dollar exchange rate and Agricultural commodity price return volatility in Nigeria using time series econometric models. The study utilizes monthly time series data on the study variables from January 2006 to April 2017 and employs the popular Augmented Dickey-Fuller unit root test and KPSS stationarity test to investigate the stationarity characteristics of the series. Simple linear regression model, Johansen Cointegration, Vector Error Correction Model (VECM), Vector Autoregressive (VAR) Granger Causality test based on Toda-Yamamoto as well as Generalized Autoregressive Conditional Heteroskedasticity (GARCH) model were employed as methods of analysis. Results showed that all the study variables are integrated of order one, I(1), crude oil prices and exchange rate are found to have a positive, significant but temporal impact on Agricultural commodity prices and there is a long-run stable relationship existing among the study variables. Crude oil prices and exchange rate are also found to Granger caused Agricultural commodity prices in Nigeria and exchange rate is found to be Granger-caused by crude oil prices. The results of the estimated GARCH (1,1) models showed that the conditional variances of Agricultural commodity prices and exchange rate log returns are stable with volatility half-lives of 1 month and 7 months respectively. While the conditional variance of crude oil prices log return series is unstable and explodes to infinity indicating that future crude oil prices cannot be predicted from the past and current prices. The study provides some policy recommendations.